1998
DOI: 10.1177/00220345980770070301
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Organ Culture Method to Study the Function of Human Odontoblasts in vitro: Gelatinase Expression by Odontoblasts is Differentially Regulated by TGF-β1

Abstract: Odontoblasts cannot be cultured by traditional cell culture methods, thus restricting in vitro studies. Here we present an organ culture method for human odonto-blasts that utilizes the pulp chamber as a culture crucible. Crowns of human third molars were dissected, pulp was gently removed, and the odontoblasts attached to and in the walls of the pulp chambers were cultured in serum-free OPTI-MEM medium, or DMEM/Ham's F12 medium containing 10% serum. Pulp tissues were cultured separately. Cell content and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 32 publications
2
104
0
3
Order By: Relevance
“…We observed reduced MMP-8 levels in obese women, which may be explained by the negative regulation of MMP-8 expression by biomolecules such as transforming growth factor-beta 1 (TGF-β1) that are elevated in obesity [28] and that strongly downregulate MMP-8 [29], while stimulating MMP-9 expression [30]. To exclude the possibility of decreased MMP-8 levels due to reduced neutrophil activation, we measured the plasma MPO activity.…”
Section: Discussionmentioning
confidence: 99%
“…We observed reduced MMP-8 levels in obese women, which may be explained by the negative regulation of MMP-8 expression by biomolecules such as transforming growth factor-beta 1 (TGF-β1) that are elevated in obesity [28] and that strongly downregulate MMP-8 [29], while stimulating MMP-9 expression [30]. To exclude the possibility of decreased MMP-8 levels due to reduced neutrophil activation, we measured the plasma MPO activity.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 years later, mature human odontoblasts were shown to express MMP-2 and MMP-9 [Tjäderhane et al, 1998b], MMP-2, MMP-9 and MMP-8 were identified in carious dentin, and the role of MMPs in the degradation of dentin collagen was demonstrated [Tjäderhane et al, 1998a]. At the same time, the activation of latent salivary pro-MMPs by exposure to low pH followed by neutralization (so-called acid activation) was also shown [Tjäderhane et al, 1998a;Sulkala et al, 2001].…”
Section: Host Proteases In Cariesmentioning
confidence: 99%
“…Only 15 years later, mature human odontoblasts were shown to express MMP-2 and MMP-9. 20,21 Resorption in the crown dentin may be due to these factors. These factors should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%